2011
DOI: 10.1007/s10802-011-9500-z
|View full text |Cite
|
Sign up to set email alerts
|

Testing Multicultural Robustness of the Child Behavior Checklist in a National Epidemiological Sample in Uruguay

Abstract: Comparisons of Child Behavior Checklist (CBCL) scores from 31 societies (Rescorla et al. Journal of Emotional and Behavioral Disorders 15:13-142 2007) supported the instrument's multicultural robustness, but none of these societies was in South America. The present study tested the multicultural robustness of the 2001 CBCL using data from a national epidemiological survey in Uruguay. Participants were 1,374 6- to 11-year-olds recruited through 65 schools nationwide; 1,098 (80%) had received no mental health or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 7 publications
5
10
2
6
Order By: Relevance
“…However, all the information in our study was reported by the parents, and more reliability would have been achieved had we used multiple informants. The CBCL scores we obtained could be considered relatively low compared to the results of previous cross-cultural studies (Viola et al 2011), especially given that we were focusing on a risk group. Thus, there may be cultural differences in reporting symptoms.…”
Section: Limitationscontrasting
confidence: 68%
“…However, all the information in our study was reported by the parents, and more reliability would have been achieved had we used multiple informants. The CBCL scores we obtained could be considered relatively low compared to the results of previous cross-cultural studies (Viola et al 2011), especially given that we were focusing on a risk group. Thus, there may be cultural differences in reporting symptoms.…”
Section: Limitationscontrasting
confidence: 68%
“…29 The Preschool Age test for 1½-5-year-old children uses the 7-syndrome model, including I, emotionally reactive; II, anxious/depressed; III, somatic complaints; IV, withdrawn; V, sleep problems; VI, attention problems; VII, aggressive behavior and other problems. Syndromes I to IV make up the internalizing syndromes, whereas VI and VII add to externalizing syndromes.…”
Section: Methodsmentioning
confidence: 99%
“…The third measure captured socio-emotional development with the Spanish version of the Child Behavioral Checklist (CBCL 1), a validated, reliable, parent-completed checklist consisting of 99 items assessing a range of problem behaviors relating to socio-emotional well-being ( Achenbach & Rescorla, 2000 ). The CBCL has been validated in Argentina and Uruguay, two Latin American countries in the same region as Chile ( Corina, 2008 ); ( Viola, Garrido, & Rescorla, 2011 ). We reversed the scale so that higher values are associated with better development outcomes, as are the scales of the other two assessments that we use.…”
Section: Methodsmentioning
confidence: 99%